2011
DOI: 10.1128/aac.01404-10
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Open-Label Investigation of the Pharmacokinetics of Daptomycin during Cardiopulmonary Bypass Surgery

Abstract: As methicillin-resistant Staphylococcus aureus (MRSA) becomes more prevalent, vancomycin is becoming increasingly used as a prophylaxis against surgical-site infections for cardiothoracic surgeries. However, vancomycin administration can be challenging, and the pharmacokinetics of alternative antibiotics in this setting are poorly understood. The primary objective of this investigation was to describe the pharmacokinetics of daptomycin in patients undergoing coronary artery bypass graft surgery. We enrolled 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Therefore, pharmacokinetics (PK) and pharmacodynamics (PD) of administered drugs can be significantly affected in setting of an extracorporeal circuit. Multiple studies conducted in patients undergoing CPB have reported on altered drug disposition [12,13,14,15]. During cardiac surgeries using CPB, patients undergo major physiological changes including hypothermia, haemodilution, reduced blood flow and pressure, release of stress-reactant hormones, fluid and electrolyte shifts, as well as release of cytokines and nitric oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pharmacokinetics (PK) and pharmacodynamics (PD) of administered drugs can be significantly affected in setting of an extracorporeal circuit. Multiple studies conducted in patients undergoing CPB have reported on altered drug disposition [12,13,14,15]. During cardiac surgeries using CPB, patients undergo major physiological changes including hypothermia, haemodilution, reduced blood flow and pressure, release of stress-reactant hormones, fluid and electrolyte shifts, as well as release of cytokines and nitric oxide.…”
Section: Introductionmentioning
confidence: 99%